ANALYSIS OF THE RISK FACTORS OF WORK FATIGUE IN FORMAL AND INFORMAL WORKERS - Rini, Willia Novita Eka; Lanita, Usi (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Labor productivity can be significantly reduced as a result of fatigue. The purpose of this study was to analyze the risk factors for work fatigue that exist in the formal and informal sector workers in Jambi City. This research was conducted using a cross-sectional design with a total sample of 200 respondents, namely 100 respondents from formal workers and 100 respondents from informal workers. The sampling technique used purposive sampling. Based on the results of the study, it can be seen that there is a significant relationship between age (p-value 0.034 PR 1.80 95% CI 1.02-3.16), length of work (p-value 0.000 PR 0.41 95% CI 0.28 - 0.59), years of service (p-value 0.001 PR 2.18 95%CI 1.33-3.56), and medical history (p-value 0.000 PR 2.07 95%CI 1.54-2, 79) with job burnout in formal and informal sector workers in Jambi City, and there is no significant relationship between gender (p-value 0.227 PR 0.79 95%CI 0.57-1.10), nutritional status (p-value 0.416 PR 1.23 95%CI 0.83-1.82), and workload (p-value 0.450 PR 0.83) 95%CI 0.58-1.20) with work fatigue in formal and informal sector workers in Jambi City. The conclusion of this study is that there is a relationship between age, length of work, years of service, and history of illness with work fatigue.